The Use of Digital Technologies for the Purpose of Improving Methodological Approaches to the Creation of a Pharmaceutical Quality System at Enterprises for the Production of Medicines - V. V. Goryachkin; V. А. Smirnov; V. N. Shestakov; R. A. Abramovich (Разработка и регистрация лекарственных средств)
Introduction. The article is devoted to the aspects of improving methodological approaches to the creation of a pharmaceutical quality system (PQS) at enterprises for the production of medicines, taking into account the possibility of using tools and means of digitalization. The relevance of the study is associated with the enduring importance of comprehensive high quality assurance in the development, production and release of medicines into circulation. The implementation of PQS requires numerous transformations of management and production processes, which can be facilitated by tools and elements of digitalization.Aim. To consider the potential and specific areas of application of digital technologies to improve the methodology and practice of developing and implementing PQS.Materials and methods. The state in the subject area was assessed on the basis of the results of economic and statistical analysis and forecasting of the implementation of PQS at Russian pharmaceutical enterprises that have positive and comparatively long experience in this area: the companies LLC "OZON" and JSC "AKRIKHIN". The assessment was carried out by calculating the integral indicator of the effectiveness of the functioning of PQS, which is a set of weighted key performance indicators (KPI) for quality.Results and discussion. The importance of the introduction of PQS for the development of pharmaceutical enterprises and the presence of numerous difficulties in the implementation of PQS, which necessitates the improvement of methodological approaches in the subject area, are stated. It has been proven that even at those enterprises where PQS has been introduced with varying degrees of success, the use of digitalization tools would contribute to a faster, more systematic and high-quality implementation of PQS. Among the key areas of application of digital tools, the authors propose monitoring of quality indicators (using neural network cards) and the use of blockchain platforms and smart contracts to register the release of drugs of appropriate quality.Conclusion. Digital tools contribute to complex improvement in many areas of socio-economic activity. Their active use at pharmaceutical enterprises is intended to contribute to ensuring the proper implementation and uninterrupted functioning of pharmaceutical quality systems, through constant monitoring of the quality of manufactured products and registration of manufactured batches in high-precision information storage systems.